2018
DOI: 10.1785/0120180123
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the New Procedures for Evaluating Parameters of Crustal Earthquakes Caused by Long Faults for Ground‐Motion Prediction

Abstract: Two new procedures for evaluating fault parameters of asperity models for predicting strong ground motions from crustal earthquakes had been proposed: one is for long strike-slip faults by Dan et al. (2011) and the other is for long reverse faults by Dan et al. (2015). The procedures are based on important statistical findings that the average dynamic stress drop is constant, 3.4 MPa on strike-slip faults with the seismic moment larger than 7.5×10 18 N-m and 2.4 MPa on reverse faults with the seismic moment la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These features for ruptures that break the entire seismogenic zone, can be explained by differences in fault rupture dynamics caused by difference in frictional properties between materials in the shallow part (weak zone) and deeper part of the crust (e.g. Pitarka et al 2009;Dalguer et al 2008;Song 2016;Dan et al 2018). The depth scaling of rise time and rupture speed prescribed in the GP2016 approach also reflects key observations where large shallow fault slip does not necessarily translate into large high-frequency motion radiation.…”
Section: Rupture Modelsmentioning
confidence: 93%
See 1 more Smart Citation
“…These features for ruptures that break the entire seismogenic zone, can be explained by differences in fault rupture dynamics caused by difference in frictional properties between materials in the shallow part (weak zone) and deeper part of the crust (e.g. Pitarka et al 2009;Dalguer et al 2008;Song 2016;Dan et al 2018). The depth scaling of rise time and rupture speed prescribed in the GP2016 approach also reflects key observations where large shallow fault slip does not necessarily translate into large high-frequency motion radiation.…”
Section: Rupture Modelsmentioning
confidence: 93%
“…The characterization of earthquake rupture has been at the forefront of new developments in numerical methods for strong ground motion simulations of crustal and subduction zone earthquakes. Analyses of recent large earthquakes indicate that multi-scale earthquake rupture models that combine large-scale, large-slip features with smaller, but effective high-frequency seismic energy generation areas, better reproduce overall characteristics of ground motion on a broad frequency range (Irikura and Kurahashi 2018;Frankel et al 2018;Iwaki et al 2016a, b;Pulido et al 2015;Dan et al 2018;Miyake et al 2003;Sekiguchi et al 2008;Graves and Pitarka 2010;Pitarka et al 2000). Schemes that include spatial correlations and interdependency of rupture parameters guided by rupture dynamics modeling offer significant advantages for use in broadband ground motion simulations (Imperatori and Mai 2013;Song 2016;Schmedes et al 2013; Graves and Pitarka 2015;Crempien and Archuleta 2017;Withers et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tables 3 and 4 lists the soil profiles for the wavenumber integration method and the stochastic Green's function method, respectively. These soil profiles were set in accordance with Sekiguchi and Iwata [2002] and Dan et al [2019], because they reproduced ground motions observed near the fault of the 1999 Kocaeli, Turkey, earthquake.…”
Section: Strong Motions Calculated By the Recipe For The Second-stage Earthquakesmentioning
confidence: 99%